Proposed Blue Ocean Strategy for OZORA Yearbook (The Indonesian Journal of Business Administration, 2020)
OZORA Yearbook is a company engaged in the creative industry in the provision of full-service yearbook making as a memory for final students in a school. Based on the 2019 report, OZORA has not been able to meet the expectations of achieving targets and continues to experience a decline in sales accompanied by a decrease in profit margins compared with the previous year. To get a picture of the company's condition, researchers collected data using qualitative methods through interviews and focus group discussions, as well as an analysis of quantitative data from the results of the customer satisfaction level questionnaire. This data is used further in analyzing the company’s business model canvas and competitor analysis to find the potential causes. Increasing competition is indicated by the price war from competitors who offer the same quality and strategy in getting customers in the same market segment. The inability to reduce costs and customer value changed, bring the company entered into a competitive red ocean. A value innovation needs to be created as a strategy for OZORA to get out from the above conditions. The researcher, together with OZORA, made a second questionnaire and mapped the results of the questionnaire into the blue ocean strategy tools and framework. The new value innovation can be a consideration for OZORA in identifying the blue ocean business strategy, to get the opportunity to expand market share and find new markets so as to improve the condition of the company. Keywords: yearbook, business model canvas, red ocean, blue ocean, value innovation, blue ocean strategy